Increase of the Adiponectin/Leptin Ratio in Patients with Obesity and Type 2 Diabetes after Roux-en-Y Gastric Bypass - Unamuno, Xabier (Nutrients, 2019)
Bariatric surgery remains the most effective option for achieving important and sustained weight loss. We explored the effects of Roux-en-Y gastric bypass (RYGB) on the circulating levels of adiponectin, leptin, and the adiponectin/leptin (Adpn/Lep) ratio in patients with obesity and type 2 diabetes (T2D). Twenty-five T2D volunteers undergoing RYGB were included in the study, and further subclassified as patients that responded or not to RYBG, regarding remission of T2D. Anthropometric and biochemical variables were evaluated before and after RYGB. Obese patients with T2D exhibited an increase (p < 0.0001) in the Adpn/Lep ratio after RYGB. Changes in the Adpn/Lep ratio correlated better with changes in anthropometric data (p < 0.001) than with the variations of adiponectin or leptin alone. Multiple regression analysis revealed that the change in the Adpn/Lep ratio in patients with T2D was an independent predictor of the changes in body mass index (p < 0.001) and body fat percentage (p = 0.022). However, the Adpn/Lep ratio did not differ between individuals with or without T2D remission after RYGB. In summary, the current study demonstrated that after weight and body fat loss following RYGB, the Adpn/Lep ratio increased in patients with obesity and T2D.